Genotoxicity of PM2.5 and PM1.0 Particulates on Human Peripheral Blood Lymphocytes in Manila, Philippines - Ma. Katrina Gale Estonilo; Joedith Anne Cazeñas; Carlos Josef Villafuerte; Custer Deocaris; Gloriamaris Caraos; Gerardo Jose Robles; Maria Cecilia Galvez; Celia Asaad; Edgar Vallar (Atmosphere, 2021)
Urban air quality is increasingly being studied as a fraction of the world’s population is living in megacities. In this study, particulate matter (PM) along Taft Avenue, Manila, the Philippines, is investigated in terms of its ability to induce genetic damage in human peripheral blood lymphocytes (PBLs). Size-segregated roadside air samples were obtained from 2015–2017 near a university gate and analyzed using in vitro micronucleus (MN) and cytokinesis-block proliferation tests. While cellular proliferation was unaffected by 0–0.1 kg/m3 of PM1.0 and PM2.5, PBL cells treated with PM2.5 displayed a significantly higher micronucleus count (p = 0.03) compared to the cells treated with PM1.0. Atomic absorption spectroscopy revealed greater amounts of Cd, Ca, Pb, K, Na, and Zn in PM2.5 compared to PM1.0. The results indicate that the differences in composition of the two size fractions of air particulates are associated with their genotoxicities.